Identificación y valoración de riesgos laborales en el laboratorio dental Juan Hernández según GTC 045 (2021)
The present degree project carried out in the Juan Hernández Dental Laboratory located in the city of Villavicencio, aimed to design the hazard matrix and risk assessment of the laboratory staff based on GTC 45, in order to establish prevention measures and control of the risks to which they are exposed in the development of activities. The identification of thehazards was carried out through open and closed interviews with the workers and through an inspection of the state of the laboratory, where it was shown that they do not use PPE, biosafety measures and that they carry out their activities without any standard procedure. Since due to lack of training they do not know the procedures for safe work, active breaks and the importance of good posture; Taking into account the matrix proposed by GTC 45, biomechanical, chemical, physical, chemical hazards and safety conditions were identified. Accordingly, prevention and control measures were proposed for each of the identified risks, to improve the health and safety conditions of the workers.